PENGARUH MORALITAS APARAT, KESESUAIAN KOMPENSASI, DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - Nurmaharani Junia; M.Rasuli '; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine and analyze the effect of apparatus morality, suitability of reward, and compliance to accounting rules on the tendency of accounting fraud. The population on this research was SKPD at Kampar Regency. The sampling technique using purposive sampling method and determination of sample size in this study was calculated by the formula slovin obtained by 99 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using simple linear regression analysis and moderated regression analysis (MRA) approach. The results of this study show that first, apparatus morality significant affect on the tendency of accounting fraud, where the significant value are 0,047<0,05. Second, the suitability of reward significant affect on the tendency of accounting fraud, where the sicnificant value are 0,034<0,05. Third, the compliance to accounting rules significant affect on the tendency of accounting fraud, where the sicnificant value are 0,33<0,05.Keywords: apparatus morality, suitability of reward, compliance to accounting rules, and tendency of accounting fraud.